Orthographic Priming in Second‐Language Visual Word Recognition. Issue 3 (6th February 2022) - Jiang, Nan; Wu, Xuesong
Abstract: Several previous studies showed that prime‐target pairs with orthographical overlap but no semantic or morphological relationship (e.g., freeze‐free ) produced a masked priming effect in second language (L2) speakers but not in first language (L1) speakers. The present study further explored this intriguing L1–L2 difference by comparing English native speakers and nonnative speakers in the masked priming paradigm in combination with a lexical decision task. The stimuli included prime‐target pairs with orthographical overlap at both the word‐initial and word‐final positions (e.g., rubber‐rub, stage‐age ) but without any semantic or morphological relationship. The results replicated orthographic priming in L2 speakers for words with both overlap positions. Two accounts of this L1–L2 difference are discussed, one focusing on the representational aspect and the other on the processing characteristics of the L2 lexicon. Abstract :